Стратегия корпоративного финансирования: ENTREPRENEURIAL ACTIVITIES AS THE BASIS FOR THE DEVELOPMENT OF THE NATIONAL ECONOMY - Aliboyev, Abror (Журнал иностранных языков и лингвистики, 2020)
Link functionality caveat The .disabled class uses pointer-events: none to try to disable the link functionality of s, but that CSS property is not yet standardized. In addition, even in browsers that do support pointer-events: none, keyboard navigation remains unaffected, meaning that sighted keyboard users and users of assistive technologies will still be able to activate these links. So to be safe, add a tabindex="-1" attribute on these links (to prevent them from receiving keyboard focus) and use custom JavaScript to disable their functionality.